Plasma-chemical synthesis of carbide-based vacuum-plasma functional coatings and study of tribological characteristics of friction pairs - Олексій Сагалович; Владислав Сагалович; Віктор Попов; Станіслав Дуднік (Mechanics and Advanced Technologies, 2024)
The work is devoted to the search for new materials with high functional characteristics using the Avinit vacuum-plasma technologies developed by us, based on the complex use of coating methods (plasma-chemical CVD, vacuum-plasma PVD (vacuum-arc, magnetron), processes of ion saturation and ion surface treatment), stimulated by non-equilibrium low-temperature plasma. Processes of controlled plasma-chemical synthesis of the formation of multicomponent coatings in "metal-carbon" systems – Avinit coating (TiC, MoC) using vacuum-arc sources of ionized atomic fluxes of titanium and molybdenum in an argon-benzene plasma environment were developed and their characteristics were studied depending on their conditions formation. Metallographic studies confirm the possibility of low-temperature application of high-quality wear-resistant high-hard "metal-carbon" coatings with a hardness of 18,000-30,000 MPa, while ensuring good adhesion to the substrate materials (steel DIN 1.2379) without reducing strength and without deteriorating the cleanliness class of the original surface. The conducted tribological tests using the "cube-roller" scheme reveal high tribological characteristics of steel DIN 1.2379 tribopairs with developed coatings and testify to the promisingness of the developed multi-component multilayer coatings Avinit (Ti-C, MoS) for increasing wear resistance and reducing the coefficient of sliding friction in friction nodes. The developed plasma-chemical vacuum-plasma coatings are applied to mock-up samples of the working compressor blades of the GTE of aircraft engines. Proven modes allow to get high-quality, uniform coatings with high adhesion. This gives reason to consider the developed process as an alternative for expanding the range of new Avinit vacuum-plasma erosion-resistant coatings and developing structures of anti-friction wear-resistant coatings to increase the performance of friction pairs in "coating-steel" and "coating-coating" systems.